Cuticular wax composition changes of 10 apple cultivars during postharvest storage. (15th September 2020) - Chai, Yifeng; Li, Ang; Chit Wai, Su; Song, Congcong; Zhao, Yaoyao; Duan, Yuquan; Zhang, Baiqing; Lin, Qiong
Highlights: Alkanes and primary alcohols decreased while fatty acids increased in stored apple. Weight loss rate was significantly correlated with wax components. Alkanes was essential for fruit storage and quality control in apple. Abstract: Cuticular wax chemicals differ among fruit cultivars and contribute to storage ability. However, wax analysis in apple cultivars, particularly during storage, has not been described. In this work, the chemicals and crystal structures of cuticular wax in 10 apple cultivars were analyzed to observe wax functions in apple during storage. Results showed that alkanes and primary alcohols decreased while fatty acids increased in stored fruits of all cultivars compared with the fruits before storage. Terpenoids, aldehydes, and phenols were observed in stored fruits but not in the fruits before storage in all cultivars except 'Red Star' fruit. The weight loss rate was significantly correlated with six components including C13 alcohol, C14 alkanes, total alkanes, total wax, C13 alkanes and C54 alkanes in 10 cultivar apple fruits during storage. Our findings indicate that the total wax, particularly alkanes, in the peel of apple fruits is essential for storage and quality control.